Implementasi Kebijakan Pemerintah Kabupaten Sumenep Dalam Rangka Pengembangan dan Pelestarian Kesenian Musik Tradisional Tong - Tong - Bagus Ananda Kurniawan; Chusnul Abady (Kanal: Jurnal Ilmu Komunikasi, 2019)
This qualitative descriptive research method is to describe and discuss a policy of the Sumenep Regency Government to implement the Sumenep Regency Government Policy in the Context of the Development and Preservation of Traditional Music Art of Tong-Tong Madura Island, East Java Province. At the beginning of the development of traditional Tong-Tong art music which was used as a sahur patrol music was played in waking people to perform the sahur worship in the holy month of Ramadan and Calling the Dwarf who wanted to go home to his cage. In accordance with the Sumenep Regent's Regulation No. 28/2008 concerning the duties and functions of the Regional Office, the Sumenep District Youth and Sports Culture Service, has the task and function of fostering and preserving the Tong-Tong Traditional Music culture in the Sumenep district. The Tong - Tong se Madura Music Contest and the Sumenep Regency Tong - Tong Festival from 2016-2018 is in the context of fostering efforts as well as preserving the cultural heritage of the ancestors which is held regularly every year starting. The cost of conducting the Tong - Ton Traditional Arts Music Kirab Music Festival, the Tong Se Madura Music Contest and the Tong-Tong Festival is annually charged to the Sumenep Regency Regional Revenue and Expenditure Budget (APBD). The aim is to hold the Tong Tong Se Madura Music Competition and the Tong-Tong Festival every year in Sumenep Regency to improve and develop Sumenep Regency tourism promotion and marketing through the Madura tong-tong music competition.